1998
DOI: 10.2214/ajr.171.2.9694463
|View full text |Cite
|
Sign up to set email alerts
|

Aortobronchial fistula occurring after coarctation repair: findings on aortography, helical CT, and CT angiography.

Abstract: F istula formation betweenthe aorta and the bronchial tree is rare; to our knowledge, only 71 cases were re

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Contrast-enhanced CT, especially multidetector CT, has been demonstrated to be a remarkably valuable diagnostic tool for helping in the diagnosis of aortic fistulas. [11][12][13][14] In a review of the published data, MacIntosh and colleagues 17 found a pseudoaneurysm at the fistula site in 73% of 63 cases of ABF. Pseudoaneurysms can result from local infection or mechanical stress on the anastomosis or graft wall that causes tight adherence and pressure necrosis of the bronchopulmonary or esophageal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast-enhanced CT, especially multidetector CT, has been demonstrated to be a remarkably valuable diagnostic tool for helping in the diagnosis of aortic fistulas. [11][12][13][14] In a review of the published data, MacIntosh and colleagues 17 found a pseudoaneurysm at the fistula site in 73% of 63 cases of ABF. Pseudoaneurysms can result from local infection or mechanical stress on the anastomosis or graft wall that causes tight adherence and pressure necrosis of the bronchopulmonary or esophageal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These signs included the presence of periaortic (ectopic) gas, an aortic pseudoaneurysm bulge, a penetrating atherosclerotic ulcer, an intramural hematoma, effacement of the periaortic or perigraft fat plane, esophageal wall thickening, and a periprosthetic collection. [11][12][13][14]…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…The treatment of PSAs complicated with ABF gradually increased in complexity over time, from direct closure of the aorta [ 20 ], to interposition of synthetic grafts [ 22 , 24 , 27 , 29 , 30 , 31 , 38 , 44 , 45 ], extra-anatomic bypasses with or without resection of the native descending thoracic aorta [ 30 , 31 , 35 ], concomitant multiple endovascular procedures (TEVAR associated with coil embolization and occlusion with transcatheter devices) [ 23 , 41 ], and hybrid approaches combining TEVAR (±other endovascular procedures) with closed-chest debranching and surgical bypasses [ 12 , 13 ]. Our case is the 3rd hybrid approach reported and the first in a SARS-CoV-2 patient.…”
Section: Discussionmentioning
confidence: 99%
“…Various imaging techniques can assist in the diagnosis of ABF. Computed tomography angiography (CTA) is the imaging technique of choice due to its accuracy and speed [ 8 ]. The cardinal symptom is haemoptysis, intermittent or massive, which may be fatal [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%